On an antiperiodic type boundary-value problem for first order nonlinear functional differential equations of non-Volterra's type - Hakl, R.; Lomtatidze, A.; Šremr, J. (Нелінійні коливання, 2003)
Nonimprovable, in a certain sense, sufficient conditions are established for the solvability and unique solvability of the boundary-value problem u'(t) = F(u)(t), u(a) + λu(b) = h(u), where F : C([a, b]; R) → L([a, b]; R) is a continuous operator satisfying the Caratheodory conditions, ` h : C([a, b]; R) → R is a continuous functional, and λ ∈ R₊.